Estimated age of the Sutural behavior in pre-Columbian Peruvian skulls with Artificial cephalic deformation - Gálvez-Calla, Luis Hernando (2016)
Objective:To estimate the age of the skulls with artificial cephalic deformation through the obliteration of the Palatine, cranial sutures and other age indicators present in the chronology of tooth eruption; es-tablishing coherent or conflicting relationship between them. Materials and method: it consisted of 18 pre-Columbian skulls in the typological classification of Pedro Weiss. Estimation of the age is based on ossification ectocraneal of the sutures of the system box cranial and lateral anterior Meindl & Lovejoy, the obliteration of Palatine by the Mann method sutures, and other indicators of age; registering grades of closure suture of each craneometricos points; rated as: 0 = open suture; 1 = minimum obliteration; 2 = significant obliteration; 3 = complete obliteration. The sum of the values obtained according to Meindl & Lovejov or the obliteration of the last midpalatal suture according to Mann or chronological eruption of teeth are the estimated age; establishing a relationship of consistency or discrepancy between them using the straight-line method. Results: the age of the skulls with artificial cephalic deformation estimated by closure of cranial sutures Meindl and express Lovejoy18 method values high on estimates by the method of Mann in palatal sutures. So the age obtained by sutural methods values express the apparent age, being the most cranial to the Palatine, probably by environmental influences. Palatal sutures and the dentition to be away from the action of the deforming Tools Express closer to the actual values; without however could be influenced by other factors (bad habits). Conclusions The results suggest that to deforming tools could have accelerated the process of ossification of cranial vault in 5 to 10 years approximate, further increasing in 15 ± 5 additional years if considered chronological indicators of tooth eruption.